Cathode active material having spinel structure
By preparing lithium transition metal oxide particles of different particle sizes and using dopants to form spinel structures, the problem of poor performance of lithium battery cathode materials in charge-discharge cycles was solved, improving energy density and stability, while reducing production costs and wastewater generation.
Patent Information
- Application Number
- CN202480025600.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-20
- Filing Date
- 2024-04-19
- Publication Date
- 2025-11-21
AI Technical Summary
Existing lithium battery cathode active materials have poor performance in multiple charge-discharge cycles, making it difficult to simultaneously improve volumetric energy density and voltage, and the production process is costly and generates a lot of wastewater.
Lithium transition metal oxide particles were prepared using two different processes. The first particle had a particle size of no more than 3 micrometers, and the second particle had a particle size of at least 3 times that of the first particle. The dopant D was selected from B, N, F, etc., to form a spinel structure. The mixing process improved the packing density and average voltage.
This achieves high energy density and stability of cathode active materials without compromising electrochemical stability, reducing production costs and wastewater generation.
Smart Images

Figure CN121001964A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a cathode active material for lithium batteries.
[0002] BACKGROUND
[0003] Developing high energy density rechargeable battery materials has been a major research topic as they have a wide range of applications in electric vehicles, portable electronics, and grid-scale energy storage. Since their first commercialization in the early 1990s, lithium-ion batteries (LIBs) have many advantages over other commercial battery technologies. In particular, their higher specific energy and specific power make LIBs the best candidate for electric mobile transportation applications.
[0004] LNMO or lithium nickel manganese oxide is a cathode material that has gained attention in the battery industry due to its promising electrochemical performance and relatively low cost compared to other high energy density cathode materials such as NCA and LCO. LNMO has a similar crystal structure to LMO but with the addition of nickel, which increases its energy density and improves its thermal stability. LNMO also has lower toxicity than other nickel-containing cathode materials, making it a more environmentally friendly option.
[0005] One of the main advantages of LNMO is its high capacity retention and cycling stability, which means it can maintain a high energy capacity over multiple charge-discharge cycles. This makes it a promising candidate for use in electric vehicle batteries, where long cycle life is critical.
[0006] The characteristics of the lithium cathode active material can be characterized by the formula: Li x Ni y Mn 2-y O 4-δ where 0.9 < x < 1.1, 0.4 < y < 0.5 and 0 < δ < 0.1. Such materials can be used, for example, in portable devices (US 8,404,381); electric vehicles, energy storage systems, auxiliary power units, and uninterruptible power supplies. The lithium cathode active material is considered a forward-looking replacement for current lithium secondary battery cathode materials, such as: LiCoO2 and LiMn2O4.
[0007] The lithium cathode active material can be prepared from a precursor obtained by a co-precipitation process. Due to the co-precipitation process, the precursor and the product are spherical. Electrochimica Acta (2014), pages 290-296 discloses a material prepared from a precursor obtained by a co-precipitation process, followed by sintering (heat treatment) at 500 °C, and subsequently at 800 °C. The obtained product has a high crystallinity and has a spinel structure after the first heat treatment step (500 °C). The product morphology is observed to be uniform, with a tap density of 2.03 g cm-3.-3 and the uniform secondary particle size is 5.6 pm. Electrochimica Acta (2004) pages 939-948 states that a uniform distribution of spherical particles has a higher tap density than irregular particles because they have a greater flowability and pack easily.
[0008] Lithium cathode active materials can also be prepared from a precursor obtained by mechanically mixing starting materials to form a homogeneous mixture as disclosed in US 8,404,381. The precursor is heated at 600 °C, annealed at 700 °C to 950 °C and cooled in an oxygen containing medium. It is disclosed that a heat treatment step at 600 °C is required to ensure that lithium is well incorporated in the mixed nickel and manganese oxide precursor. It is further disclosed that the annealing step is usually performed at a temperature higher than 800 °C to cause oxygen loss while producing the desired spinel morphology. It is further disclosed that the subsequent cooling in an oxygen containing medium enables a partial recovery of oxygen. US 7,754,384 does not mention the tap density of the material. It is also disclosed that a 1 mol% to 5 mol% excess of lithium is used to prepare the precursor.
[0009] US 7,754,384 also teaches a material having the formula LiNi 0.4 Mn 1.6 O 4-δ wherein δ > 0. It is disclosed that a material having a given formulation, i.e. a low content of Ni compared to Mn, has a high cycle stability.
[0010] J. Electrochem. Soc. (1997) 144, pages 205-213 also discloses the preparation of spinel LiNi 0.5 Mn 1.5 O4from a precursor, the precursor being prepared from mechanically mixing starting materials to obtain a homogeneous mixture. The precursor is heated at 750 °C in air three times and at 800 °C once. It is disclosed that LiNi 0.5 Mn 1.5 O4loses oxygen and is out of proportion when heated above 650 °C; however, the stoichiometry of LiNi 0.5 Mn 1.5 O4is recovered by a slow cooling rate in an oxygen containing atmosphere.
[0011] WO2020 / 127543 discloses a lithium cathode active material for high voltage secondary batteries, wherein the lithium cathode active material comprises at least 94 wt% of a spinel having a net chemical composition of Li x Ni y Mn 2-yO4, wherein 0.95 < x < 1.05 and 0.43 < y < 0.47. The lithium cathode active material consists of spherical particles. The material has a high capacity, a high voltage and a low degradation relative to Li / Li + a high voltage and a low degradation.
[0012] It is desirable to provide a cathode active material having an improved volumetric energy density and / or a higher voltage and / or a high energy density. It is desirable to provide a cathode active material having an improved performance over multiple charge and discharge cycles. SUMMARY
[0013] In one aspect, a cathode active material is provided, comprising: (a) first crystalline particles, wherein the first crystalline particles have a spinel structure and have the formula Li x Ni y Mn 3-x-y- z D z O4, wherein 0.95 < x < 1.05; and 0.45 < y < 0.50, and 0 < z < 0.20, wherein D is a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof, and the first crystalline particles have a particle size of no more than 3 pm, measured as the arithmetic mean of the minimum Feret diameter of the particles using a scanning electron microscope, (b) second crystalline particles, wherein the second crystalline particles comprise a material having a spinel structure having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’ O4, wherein: 0.95 < x' < 1.05; 0.43 < y' < 0.47 and 0 < z' < 0.20, wherein D' is a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof, and the average particle size of the second crystalline particles is at least 3 times the average particle size of the first crystalline particles, measured as the arithmetic mean of the minimum Feret diameter of the particles using a scanning electron microscope, wherein y > y'.
[0014] The material of the present invention can be prepared by two different processes forming the first crystalline particles and the second crystalline particles, which can then be combined.
[0015] In another aspect, the present invention provides a process for preparing a cathode active material as described herein, comprising: A. Preparing one or more single crystals of the first component, comprising the steps of: (i) providing one or more lithium precursor compounds and one or more transition metal precursor compounds, (ii) contacting and milling the precursor compounds to form a milled mixture; (iii) calcining the milled mixture to provide a calcined mixture; B. Preparing second crystalline particles of the cathode active material, comprising the steps of: (i) providing one or more transition metal compounds, (ii) precipitating the transition metal to form a precipitate, and washing the precipitate to form a first precursor mixture; (iii) contacting the first precursor mixture with one or more lithium precursor compounds to form a second precursor mixture, and (iv) calcining the second precursor mixture.
[0016] C. Combining the products obtained in A and B.
[0017] Surprisingly, it has been found that the cathode active material of the present invention is able to achieve a high Ni content in the cathode without sacrificing the electrochemical stability due to the mixing of the above-mentioned materials with different Ni content. Thus, an increased packing density and a higher average voltage are achieved at the same time, which results in a higher energy density without compromising other properties of the cathode active material
[0018] Furthermore, it has been found that the material of the present invention has a higher stability compared to existing cathode active materials, in particular higher than cathode active materials containing only “polycrystalline materials” (such as those disclosed in WO 2020 / 127543). In fact, in some aspects, it has been found that the cathode active material of the present invention has a similar stability as single crystalline materials. The cathode active material of the present invention also provides improvements in the process of its production in terms of reduced costs and / or reduced waste water generation.
[0019] BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1. SEM image of the small-Ni435 sample of Example 1.
[0021] Figure 2. SEM image of the large-Ni435 sample of Example 3.
[0022] Figure 3: SEM image of the sample small-Ni435 after embedding in epoxy resin and polishing to a flat surface.
[0023] Figure 4: SEM image of a cross-section of an electrode made from a 50:50 mixture of small-Ni435 and large-Ni435.
[0024] Figure 5: Compacted density as a function of compaction pressure for small-Ni435 (light grey symbols), large-Ni435 (black symbols), and a 50:50 mixture of large- and small-Ni435.
[0025] Figure 6: LNMO - Li half-cell with single material. Voltage profile recorded at 0.1 C charge and 0.1 C discharge.
[0026] Figure 7: LNMO - Li half-cell with single material. Discharge capacity change at 23 °C recorded at 0.5 C charge and 1 C discharge.
[0027] Figure 8: LNMO - Li half-cell with mixed materials. Voltage profile recorded at 0.1 C charge and 0.1 C discharge.
[0028] Figure 9: LNMO - Li half-cell with mixed materials. Discharge capacity change at 23 °C recorded at 0.5 C charge and 1 C discharge.
[0029] Figure 10: LNMO - LTO full cell. Voltage profile recorded at 0.1 C charge and 0.1 C discharge.
[0030] Figure 11: LNMO - LTO full cell. Discharge capacity change at 23 °C during 1 C charge and 1 C discharge cycling. The reference cycle shown was recorded at 0.1 C charge and 0.1 C discharge. The capacity loss per 100 cycles corresponds to 1.4% for voltages between 1.7 V and 3.4 V, and to 1.1% for voltages between 2.8 V and 3.4 V.
[0031] Figure 12: Spinel degradation as a function of Ni content for small- and large- LNMO cathode active materials.
[0032] Figure 13: Discharge and charge voltage profile as a function of capacity for LNMO - Li cells.
[0033] Figure 14: Correlation between the 4 V plateau determined electrochemically and the lattice parameter a determined by X-ray diffraction.
[0034] Figure 15: Correlation between the nickel content in the spinel determined electrochemically and the lattice parameter a determined by X-ray diffraction. DETAILED DESCRIPTION
[0036] As described herein, a cathode active material is provided, comprising: (a) first crystalline particles, wherein the first crystalline particles have a spinel structure and have the formula Li x Ni y Mn 3-x-y- zD z O4, wherein 0.95 < x < 1.05; and 0.45 < y < 0.50, and 0 < z < 0.20, wherein D is a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof, and the first crystalline particles have a particle size of no more than 3 pm, measured as the arithmetic average of the smallest Feret diameter of the particles measured using a scanning electron microscope, (b) second crystalline particles, wherein the second crystalline particles comprise a material having a spinel structure having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’ O4, wherein: 0.95 < x' < 1.05; 0.43 < y' < 0.47 and 0 < z' < 0.20, wherein D' is a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof, and the average particle size of the second crystalline particles is at least 3 times the average particle size of the first crystalline particles, measured as the arithmetic average of the smallest Feret diameter of the particles measured using a scanning electron microscope, wherein y > y'.
[0037] We have found that by providing such a mixture of materials, we are able to provide a positive electrode active material which has both an improved tap density and a higher average voltage, which results in a higher energy density, without compromising other properties of the positive electrode active material.
[0038] As described herein, the positive electrode active material comprises particles formed from one or more single crystals of the first crystalline particles, which have a particle size of no more than 3 pm, measured as the arithmetic average of the smallest Feret diameter of the particles measured using a scanning electron microscope.
[0039] The skilled person will appreciate that the Feret diameter is the distance between two parallel lines placed opposite each other as tangents on the profile of a particle. The smallest Feret diameter is the smallest distance between two such tangents and can be considered as the smallest mesh size that the particular particle can pass through, e.g. for a rectangular particle, the smallest Feret diameter corresponds to the shortest side, and for a circle, the smallest Feret diameter corresponds to the diameter of the circle.
[0040] Feret diameter of particles is well known to the person skilled in the art. Feret diameter is used to analyze particle size and its distribution and has been common in scientific literature since the 1970s. Feret diameter is a measure of the size of an object defined as the distance between two parallel planes that just contain the object perpendicular to that direction. It is therefore also referred to as caliper diameter, referring to the measurement of the size of an object with a caliper.
[0041] The first or second crystalline particles can be evaluated by scanning electron microscopy (SEM) to determine the Feret diameter. For example, to prepare the material for such a measurement, it is embedded in epoxy resin and polished to a flat surface in order to image the cross-section of individual particles making up the sample. The images obtained in this way are then analyzed to measure the size and shape of the particles. The smallest Feret diameter is the smallest distance between two such tangents and can be considered as the smallest mesh size that the particular particle can pass through, e.g. for a rectangular particle the smallest Feret diameter corresponds to the shortest side and for a circular one the smallest Feret diameter corresponds to the diameter of the circle.
[0042] The size of irregularly shaped particles can also be quantified with reference to the diameter of a circle of equal projected area. For a particle of projected area A, the equal area circle thus has a diameter d = 2 √(A / (2 π)).
[0043] The Feret diameter of the particles can be determined according to the following method. Samples for scanning electron microscopy (SEM) are prepared by embedding the material in epoxy resin and polishing to a flat surface. SEM images are acquired on a Zeiss Gemini SEM 500 equipped with a field emission gun (FEG) using an acceleration voltage of 10 kV and an energy selective backscatter (ESB) detector, which is a backscatter electron detector type. The pixel size is 0.01 pm per pixel. A total of 25 images are acquired and stitched into a high resolution image of 4930 pixels x 3697 pixels corresponding to an image area of 48 pm 36 pm. The images are analyzed according to the following procedure, detecting and analyzing a total of 663 particles. The images are analyzed using ImageJ software (https: / / imagej.nih.gov). The procedure is as follows: - Threshold conversion and segmentation using the "Otsu algorithm" - Application of binary process, "Fill holes" - Application of binary process, "Erode" 8 times - Application of binary process, "Dilate" 6 times.
[0044] - Use of "Analyze Particles" without size limit
[0045] The fill hole is used to fill possible holes inside the particles. Etching is used followed by an expansion step to remove possible noise and ensure that tightly packed particles are separated.
[0046] “Spinel” refers to a crystal lattice in which oxygen is arranged in a slightly distorted cubic close-packed lattice, which can be slightly distorted, and cations occupy the interstitial octahedral and tetrahedral sites in the lattice. Oxygen and octahedrally coordinated cations form a framework structure with a three-dimensional channel system, which occupies tetrahedrally coordinated cations. The ratio between tetrahedrally coordinated cations and octahedrally coordinated cations is about 1 :2, and the ratio of cations to oxygen for a spinel-type structure is about 3:4. The cations in the octahedral sites can consist of a single element or a mixture of different elements. If the mixture of different types of octahedrally coordinated cations itself forms a three-dimensional periodic lattice, the spinel is called an ordered spinel. If the cations are more randomly distributed, the spinel is called a disordered spinel. Examples of ordered and disordered spinels are described in P4332 and Fd-3m space groups, respectively, described in Adv. Mater. (2012) 24, pp. 2109-2116.
[0047] The phase composition of the cathode active material can be determined from X-ray diffraction patterns obtained in θ-2θ geometry using a Phillips PW1800 instrument system working in Bragg-Brentano mode using Cu Kα radiation (λ = 1.541 Å). The observed data need to be corrected for experimental parameters that cause a shift of the observed data. This is achieved using the full profile fundamental parameter method implemented in TOPAS software from Bruker. The phase composition determined from the Rietveld analysis is given in weight %, with a typical uncertainty of 1-2 percentage points, and represents the relative composition of all crystalline phases. Therefore, any amorphous phase is not included in the phase composition.
[0048] For ease of reference, these and other aspects of the present application are now discussed under appropriate chapter headings. However, the teachings under each chapter are not necessarily limited to each particular chapter.
[0049] First crystalline particles - small-LNMO
[0050] The first crystalline particles of the present application have a spinel structure, having the formula Li x Ni y Mn 3-x-y-z D zO4, where 0.95 < x < 1.05; and 0.45 < y < 0.50, and 0 < z < 0.20. D is a dopant selected from B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof. The first crystalline particles have a particle size of no more than 3 pm, measured as the arithmetic average of the minimum Feret diameter of the particles measured using a scanning electron microscope. The first crystalline particles can be ordered (space group P4332) or disordered.
[0051] In one aspect, the first crystalline particles have a particle size of no more than 2.5 pm, measured as the arithmetic average of the minimum Feret diameter of the particles measured using a scanning electron microscope, for example no more than 2 pm, for example no more than 1.8 pm, for example no more than 1.6 pm, for example no more than 1.4 pm, for example no more than 1.2 pm, for example no more than 1 pm, for example no more than 0.8 pm.
[0052] In one aspect, the first crystalline particles have a particle size of at least 0.1 pm, measured as the arithmetic average of the minimum Feret diameter of the particles measured using a scanning electron microscope, for example at least 0.2 pm, for example at least 0.3 pm, for example at least 0.4 pm, for example at least 0.5 pm, for example at least 0.6 pm, for example at least 0.7 pm.
[0053] In one aspect, the first crystalline particles have a particle size of at least 0.1 pm to 2.5 pm, measured as the arithmetic average of the minimum Feret diameter of the particles measured using a scanning electron microscope, for example 0.1 pm to 2 pm, for example 0.1 pm to 1.8 pm, for example 0.1 pm to 1.6 pm, for example 0.1 pm to 1.4 pm, for example 0.1 pm to 1.2 pm, for example 0.1 pm to 1 pm, for example 0.1 pm to 0.8 pm.
[0054] In one aspect, the first crystalline particles have a particle size of at least 0.2 pm to 2.5 pm, measured as the arithmetic average of the minimum Feret diameter of the particles measured using a scanning electron microscope, for example 0.3 pm to 2.5 pm, for example 0.4 pm to 2.5 pm, for example 0.5 pm to 2.5 pm, for example 0.6 pm to 2.5 pm, for example 0.7 pm to 2.5 pm.
[0055] As described herein, the size of an irregularly shaped particle can also be quantified with reference to the diameter of an equivalent projected area circle. For a particle having a projected area of A, the equivalent area circle thus has a diameter d = 2 √(A / (2 In one aspect, the cathode active material comprises first crystalline particles, wherein the average equivalent circular diameter of the particles, as measured using a scanning electron microscope, is not greater than 3 µm. In another aspect, the average equivalent circular diameter of the particles, as measured using a scanning electron microscope, is not greater than 2.5 µm, for example not greater than 2 µm, for example not greater than 1.8 µm, for example not greater than 1.6 µm, for example not greater than 1.4 µm, for example not greater than 1.2 µm, for example not greater than 1 µm, for example not greater than 0.9 µm.
[0056] In one aspect, the average equivalent circle diameter of the first crystal particle, as measured using a scanning electron microscope, is at least 0.1 µm, for example at least 0.2 µm, for example at least 0.3 µm, for example at least 0.4 µm, for example at least 0.5 µm, for example at least 0.6 µm, for example at least 0.7 µm.
[0057] In one aspect, the average equivalent circular diameter of the first crystal particle, as measured using a scanning electron microscope, is 0.1 µm to 2.5 µm, for example 0.1 µm to 2 µm, for example 0.1 µm to 1.8 µm, for example 0.1 µm to 1.6 µm, for example 0.1 µm to 1.4 µm, for example 0.1 µm to 1.2 µm, for example 0.1 µm to 1 µm, for example 0.1 µm to 0.9 µm.
[0058] In one aspect, the average equivalent circular diameter of the first crystal particle, as measured using a scanning electron microscope, is 0.2 µm to 2.5 µm, for example 0.3 µm to 2.5 µm, for example 0.4 µm to 2.5 µm, for example 0.5 µm to 2.5 µm, for example 0.6 µm to 2.5 µm, for example 0.7 µm to 2.5 µm.
[0059] In formula Li x Ni y Mn 3-x-y-z D z In O4, x is 0.95 to 1.05. In one aspect, x is 0.95 to 1.04, for example 0.95 to 1.03, for example 0.95 to 1.02, for example 0.95 to 1.01, for example 0.95 to 1. In one aspect, x is 0.96 to 1.05, for example 0.97 to 1.05, for example 0.98 to 1.05, for example 0.99 to 1.05, for example 1 to 1.05. In one aspect, x is 0.96 to 1.04, for example 0.97 to 1.03, for example 0.98 to 1.02, for example 0.99 to 1.01, for example 0.97 to 1.02, for example 0.97 to 1.01, for example 0.97 to 1, for example 1.
[0060] In formula Li x Ni y Mn 3-x-y-z D z O4, y is 0.45 to 0.50. In an aspect, y is 0.46 to 0.50, such as 0.47 to 0.50, such as 0.48 to 0.50, such as 0.49 to 0.50, such as 0.50. In an aspect, y is 0.45 to 0.49, such as 0.45 to 0.48, such as 0.45 to 0.47, such as 0.45 to 0.46, such as 0.45.
[0061] In formula Li x Ni y Mn 3-x-y-z D z O4, z is 0 to 0.20. In an aspect, z is 0 to 0.18, such as 0 to 0.16, such as 0 to 0.15, such as 0 to 0.14, such as 0 to 0.12, such as 0 to 0.1, such as 0 to 0.08, such as 0 to 0.06, such as 0 to 0.05, such as 0 to 0.04, such as 0 to 0.03, such as 0 to 0.02, such as 0 to 0.01, such as 0.
[0062] D is a dopant, and it is clear that when z is 0, D is not present. D can be a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof. In an aspect, D is selected from the group consisting of B, Mg, Al, Nb, Si, P, La, S, Ti, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof.
[0063] In an aspect, the first crystalline particles are single crystalline particles. As described herein, the first crystalline particles of the present application have a spinel structure having the formula Li x Ni y Mn 3-x-y-z D z O4. Those skilled in the art will appreciate that a crystalline particle having a spinel structure is primarily a spinel structure, but other non-spinel structure materials can also be present in the crystal. In an aspect, the first crystalline particles comprise a material having a spinel structure having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’O4, and the content of the material is at least 94 wt.%, for example the content of the material is at least 96 wt.%, for example the content of the material is at least 98 wt.%, for example the content of the material is at least 99 wt.%, for example the content of the material is at least 99.5 wt.%, for example the content of the material is at least 99.9 wt.%, for example the content of the material is at least 99.99 wt.% based on the weight of the second crystalline particles.
[0064] Second crystalline particles large-LNMO
[0065] The second crystalline particles of the present application comprise a material having a spinel structure having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’ O4, wherein: 0.95 < x’ < 1.05; 0.43 < y’ < 0.47, and 0 < z’ < 0.20. D is a dopant selected from B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof. The second crystalline particles can be disordered (space group Fd-3m).
[0066] In one aspect, the second crystalline particles are formed from aggregated single crystals. In one aspect, the second crystalline particles are polycrystalline second particles.
[0067] The second particles can have any suitable size, so long as the average particle size of the second crystalline particles is at least 3 times the average particle size of the first crystalline particles. In one aspect, the one or more second particles have an average particle size (D50) of less than 50 µm, for example less than 45 µm, for example less than 40 µm, for example less than 35 µm, for example less than 30 µm, for example less than 25 µm, for example less than 20 µm, for example less than 15 µm, for example less than 10 µm.
[0068] In one aspect, the one or more second particles have an average particle size (D50) of at least 1 µm, for example at least 2 µm, for example at least 3 µm, for example at least 4 µm, for example at least 5 µm, for example at least 10 µm.
[0069] In one aspect, the one or more second particles have an average particle size (D50) of 4 µm to 50 µm, for example 4 µm to 45 µm, for example 4 µm to 40 µm, for example 4 µm to 35 µm, for example 4 µm to 30 µm, for example 4 µm to 25 µm, for example 4 µm to 20 µm, for example 4 µm to 15 µm, for example 4 µm to 10 µm.
[0070] One method for quantifying particle size is to plot the entire particle size distribution, which is a curve showing the volume fraction of particles of a specific size as a function of particle size. In this distribution, D10 is defined as the particle size at which 10% of the population distribution is below the D10 value, D50 is defined as the particle size at which 50% of the population distribution is below the D50 value (i.e., the median), and D90 is defined as the particle size at which 90% of the population distribution is below the D90 value. Common methods for determining particle size distribution include laser diffraction measurements and scanning electron microscopy measurements, combined with image analysis. The definition and measurement of the particle size distribution value D50 are described in Jillavenkatesa A, Dapkunas SJ, Lin-Sien Lum: Particle Size Characterization, NIST (National Institute of Standards and Technology) Special Publication 960-1, 2001.
[0071] In formula Li x’ Ni y’ Mn 3-x’-y’-z’ D' z’ In O4, x is 0.95 to 1.05. In one aspect, x' is 0.95 to 1.04, for example 0.95 to 1.03, for example 0.95 to 1.02, for example 0.95 to 1.01, for example 0.95 to 1. In one aspect, x' is 0.96 to 1.05, for example 0.97 to 1.05, for example 0.98 to 1.05, for example 0.99 to 1.05, for example 1 to 1.05. In one aspect, x' is 0.96 to 1.04, for example 0.97 to 1.03, for example 0.98 to 1.02, for example 0.99 to 1.01, for example 0.97 to 1.02, for example 0.97 to 1.01, for example 0.97 to 1, for example 1.
[0072] In formula Li x’ Ni y’ Mn 3-x’-y’-z’ D' z’ In O4, y' is 0.43 to 0.47. In one aspect, y' is 0.44 to 0.47, for example 0.45 to 0.47, for example 0.46 to 0.47, for example 0.45 to 0.46, for example 0.45. In another aspect, y' is 0.43 to 0.46, for example 0.43 to 0.45, for example 0.43 to 0.44.
[0073] In formula Li x’ Ni y’ Mn 3-x’-y’-z’ D' z’In O4, z' is from 0 to 0.20. In one aspect, z' is from 0 to 0.18, such as from 0 to 0.16, such as from 0 to 0.15, such as from 0 to 0.14, such as from 0 to 0.12, such as from 0 to 0.1, such as from 0 to 0.08, such as from 0 to 0.06, such as from 0 to 0.05, such as from 0 to 0.04, such as from 0 to 0.03, such as from 0 to 0.02, such as from 0 to 0.01, such as 0.
[0074] D' is a dopant, and it is clear that when z is 0, D' is not present. D' can be a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof. In one aspect, D' is selected from the group consisting of B, Mg, Al, Nb, Si, P, La, S, Ti, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof.
[0075] As described herein, the second crystalline particle of the present application comprises a material having a spinel structure having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D' z’ O4. In one aspect, the second crystalline particle comprises a material having a spinel structure having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D' z’ O4, and the content of the material is at least 50 wt.%, such as the content of the material is at least 55 wt.%, such as the content of the material is at least 60 wt.%, such as the content of the material is at least 60 wt.%, such as the content of the material is at least 65 wt.%, such as the content of the material is at least 70 wt.%, such as the content of the material is at least 75 wt.%, such as the content of the material is at least 80 wt.%, such as the content of the material is at least 85 wt.%, such as the content of the material is at least 90 wt.%, such as the content of the material is at least 92 wt.%, such as the content of the material is at least 94 wt.%, such as the content of the material is at least 96 wt.%, such as the content of the material is at least 98 wt.%, such as the content of the material is at least 99 wt.%, such as the content of the material is at least 99.5 wt.%, based on the weight of the second crystalline particle.
[0076] Positive active material
[0077] As described herein, in one aspect, a cathode active material is provided comprising two types of lithium transition metal oxide particles having the general formula Li x Ni y Mn 3-x-yO4, and further comprising an optional dopant (D). The lithium transition metal oxide can have a spinel crystal structure. The cathode active material comprises: (i) particles formed from one or more single crystals, wherein the arithmetic mean of the minimum Feret diameter of the particles, as measured using a scanning electron microscope, is not greater than 3 pm, and 0.95 < x < 1.05; 0.45 < y < 0.50 (ii) second particles that can be formed from aggregated single crystal particles, and 0.95 < x < 1.05; 0.43 < y < 0.47.
[0078] In one aspect, the first crystalline particles have a particle size of 0.5 pm to 2 pm, as measured as the arithmetic mean of the minimum Feret diameter of the particles, as measured using a scanning electron microscope; and the second crystalline particles have an average particle size of 5 pm to 10 pm, as measured as the arithmetic mean of the minimum Feret diameter of the particles, as measured using a scanning electron microscope.
[0079] In one aspect, the first crystalline particles have a particle size of not greater than 1 pm, as measured as the arithmetic mean of the minimum Feret diameter of the particles, as measured using a scanning electron microscope; and the second crystalline particles have an average particle size of at least 3 pm, as measured as the arithmetic mean of the minimum Feret diameter of the particles, as measured using a scanning electron microscope.
[0080] In one embodiment, the second particles of the cathode active material have a porosity of less than 8%, for example a porosity of less than 6%, for example a porosity of less than 4%, for example a porosity of 1% to 3%. As will be appreciated by the skilled person, the porosity can be determined by measuring the particle density using a pycnometer with ethanol. The porosity of a material is equal to 1 - (particle density / skeleton density). For reference, the skeleton density of LNMO is 4.43 g / cm 3 .
[0081] In one aspect, the first crystalline particles are present in an amount of 20 wt.% to 80 wt.%, for example in an amount of 30 wt.% to 80 wt.%, for example in an amount of 30 wt.% to 70 wt.%, for example in an amount of 35 wt.% to 70 wt.%, for example in an amount of 35 wt.% to 65 wt.%, for example in an amount of 35 wt.% to 60 wt.%, for example in an amount of 35 wt.% to 55 wt.%, for example in an amount of 35 wt.% to 50 wt.%, based on the weight of the cathode active material.
[0082] In one aspect, the second crystalline particles are present in an amount of 20 wt.% to 80 wt.%, for example in an amount of 30 wt.% to 80 wt.%, for example in an amount of 30 wt.% to 70 wt.%, for example in an amount of 35 wt.% to 70 wt.%, for example in an amount of 35 wt.% to 65 wt.%, for example in an amount of 35 wt.% to 60 wt.%, for example in an amount of 35 wt.% to 55 wt.%, for example in an amount of 35 wt.% to 50 wt.%, based on the weight of the cathode active material.
[0083] Method
[0084] The material of the present application can be prepared by two different methods of forming the first crystalline particles and the second crystalline particles, which can then be combined.
[0085] In the first method, the preparation of one or more single crystals of a first component is provided, comprising the steps of: (i) providing one or more lithium precursor compounds and one or more transition metal precursor compounds, (ii) contacting and milling the precursor compounds to form a milled mixture; (iii) calcining the milled mixture to provide a calcined mixture; The lithium precursor compounds of the first method can be selected from Li2CO3 or LiOH H2O The transition metal precursor compounds of the first method can be selected from any oxide of Mn and Ni, carbonates of Mn and Ni, and hydroxides of Mn and Ni. In one aspect, the transition metal precursor compounds of the first method are selected from MnO2, Mn3O4, MnCO3, NiCO3, and basic nickel carbonate such as (Ni(CO3)x(OH)y.zH2O, where (2x+y=2)); and mixtures thereof.
[0086] In one aspect, the milled mixture is calcined at a temperature of at least 800 °C. In embodiments of the method, the milled mixture is calcined at a temperature of 300 °C to 1200 °C, such as 400 °C to 1100 °C, such as 500 °C to 1100 °C, such as 500 °C to 1000 °C, such as 600 °C to 1000 °C, such as 700 °C to 950 °C.
[0087] The milled mixture can be calcined for any suitable period of time. In one aspect, the milled mixture is calcined for a period of at least 10 minutes, such as at least 30 minutes, such as at least 1 hour, such as at least 2 hours, such as at least 3 hours. In one aspect, the milled mixture is calcined for a period of 10 minutes to 10 hours, such as 30 minutes to 10 hours, such as 1 hour to 10 hours, such as 2 hours to 10 hours, such as 3 hours to 10 hours.
[0088] After calcining the milled mixture, it is typically cooled. By "cooling" is meant processing the material at a gradually decreasing temperature or temperature range to reduce the temperature of the material. Typical cooling conditions are 1 °C to 5 °C per minute as the temperature is reduced from 900 °C to 700 °C. Optionally, the material can be cooled to, for example, 600 °C, 500 °C, 400 °C, 300 °C, 200 °C, 100 °C, 50 °C, room temperature (i.e., about 25 °C).
[0089] The second method is for preparing the second crystalline particles of the positive electrode active material. The method comprises the following steps: (i) providing one or more transition metal compounds, (ii) precipitating the transition metal to form a precipitate, and washing the precipitate to form a first precursor mixture; (iii) contacting the first precursor mixture with one or more lithium precursor compounds to form a second precursor mixture, and (iv) calcining the second precursor mixture.
[0090] As will be appreciated by the skilled person, step (ii) results in the production of waste water during the washing process.
[0091] The lithium precursor compound can be selected from the group consisting of Li2CO3, LiOH H2O and LiNO3, and mixtures thereof.
[0092] The transition metal precursor compound of the second method can be selected from compounds of Ni and Mn that are soluble in water. In one aspect, the transition metal precursor compound is selected from the group consisting of MnSO4, Mn(NO3)2, NiSO4, Ni(NO3)2, and mixtures thereof.
[0093] In one aspect, the second precursor mixture is dried prior to step (iv), i.e. calcining the second precursor mixture.
[0094] In one aspect, the second precursor mixture is calcined in a reducing atmosphere at a temperature of at least 500 °C, followed by calcination in air at a temperature of at least 800 °C.
[0095] In embodiments of the method, the second precursor mixture is calcined at a temperature of from 300 °C to 1200 °C, such as from 400 °C to 1100 °C, such as from 500 °C to 1100 °C, such as from 500 °C to 1000 °C, such as from 600 °C to 1000 °C, such as from 700 °C to 900 °C.
[0096] The second precursor mixture can be calcined for any suitable period of time. In one aspect, the second precursor mixture is calcined for a period of at least 10 minutes, such as at least 30 minutes, such as at least 1 hour, such as at least 2 hours, such as at least 3 hours, such as at least 4 hours, such as at least 5 hours, such as at least 6 hours, such as at least 7 hours, such as at least 8 hours, such as at least 9 hours, such as at least 10 hours. In one aspect, the second precursor mixture is calcined for a period of 10 minutes to 20 hours, such as 30 minutes to 20 hours, such as at least 1 hour to 20 hours, such as at least 2 hours to 20 hours, such as at least 3 hours to 20 hours, such as at least 4 hours to 20 hours, such as at least 5 hours to 20 hours, such as at least 6 hours to 20 hours, such as at least 7 hours to 20 hours, such as at least 8 hours to 20 hours, such as at least 9 hours to 20 hours, such as at least 10 hours to 20 hours.
[0097] After calcining the second precursor mixture, it is typically cooled. "Cooling" refers to the process of a material being treated at a gradually decreasing temperature or temperature range to reduce the temperature of the material. Typical cooling conditions are 1 °C to 5 °C per minute when the temperature is reduced from 900 °C to 700 °C. Optionally, the material can be cooled to, for example, 600 °C, 500 °C, 400 °C, 300 °C, 200 °C, 100 °C, 50 °C, room temperature (i.e., about 25 °C).
[0098] In one embodiment, the intermediate further comprises up to 3 mol% of other elements in addition to Li, Ni, Mn, and O. This is characterized in the formula of the present patent as elements D and D', and these elements can be, for example, one or more of the following: B, N, F, Mg, Al, Si, P, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, any mixture thereof, or any chemical composition containing one or more of these compounds. The dopants can originate from additions or impurities in the starting materials.
[0099] "precursor" refers to a composition prepared by, for example, mechanical mixing and co-precipitation prior to heat treatment at a temperature of, for example, 300 °C to 1000 °C.
[0100] "Press density" is a selected measurement value in the present application in relation to the definition of powder density. The powder can be compacted or loose into a larger range of bulk density (compared to coarser granular material). It can become very dense when vibrated or compressed, even losing its flow ability. The measurement of "press density" of the cathode active material powder in the present invention is described in Example 7, and the results are shown in Figure 5 and Tables 1-3.
[0101] A "reducing atmosphere" refers to an atmosphere that, at the relevant heat treatment temperature, shifts the thermodynamic equilibrium of the solid towards a phase distribution with an average oxidation state of the metal lower than the spinel phase. The reducing atmosphere can be provided by the type of gas present within the reaction vessel during heating. Such a gas can be provided by the presence of a reducing gas; for example, the reducing gas can be one or more selected from the group consisting of: hydrogen; carbon monoxide; carbon dioxide; nitrogen; an inert gas having less than 15 vol% oxygen; and mixtures thereof. The term "an inert gas having less than 15 vol% oxygen" is meant to encompass inert gases having 0 vol% oxygen (corresponding to an inert gas without oxygen) up to 15 vol% oxygen. Preferably, the amount of oxygen in the reducing atmosphere is low, for example, less than 1000 ppm, and most preferably less than 10 ppm. Typically, no oxygen will be added to the atmosphere; however, oxygen can be formed during heating.
[0102] An "inert gas" refers to a gas that does not participate in the process. Examples of inert gases include one or more gases selected from the group consisting of: argon; nitrogen; helium; and mixtures thereof.
[0103] Furthermore, the term "reducing atmosphere" is meant to include compositions comprising two or more gases, wherein one gas, when used independently of the other gas, is considered a non-reducing atmosphere gas, and the second gas or species reduces the oxidation potential of the gas mixture. The overall reducing capacity of the atmosphere corresponds to the reducing atmosphere. Such compositions can be selected from the following gases: nitrogen, an inert gas having less than 15 vol% oxygen, air, and hydrogen; air and CO; air and methanol; air and carbon dioxide.
[0104] Furthermore, a "reducing atmosphere" can be obtained by adding a substance to the precursor composition or by adding a gaseous composition to the atmosphere to remove all or part of any oxidizing species present in the atmosphere of the reaction vessel during heating. The substance can be added to the precursor during preparation or prior to heat treatment. The substance can be any material that can be oxidized, and preferably comprises carbon; for example, the substance can be one or more compounds selected from the group consisting of graphite, acetic acid, carbon black, oxalic acid, wood fibers, and plastic materials.
[0105] A "non-reducing atmosphere" refers to an atmosphere in which the thermodynamic equilibrium of the solid is completely shifted towards the spinel phase when the temperature is below 700°C.
[0106] In one embodiment, the non-reducing atmosphere is a gaseous composition selected from the group consisting of air and a composition comprising at least 5 vol% oxygen in an inert gas. The reducing atmosphere can be provided by the type of gas present within the reaction vessel during heating. Preferably, the non-reducing gas is air.
[0107] “Calcining” refers to the treatment of a material at a temperature or temperature range to obtain a desired crystallinity. The temperature or temperature range is intended to indicate the temperature of the material being heat treated. Typical calcination temperatures are about 500°C, about 600°C, about 700°C, about 800°C, about 900°C, about 1000°C, and temperature ranges are about 300°C to about 1200°C; about 500°C to about 1000°C; 650°C to 950°C. The term “calcined at a temperature of X°C to Y°C” does not mean to limit to one specific temperature from X to Y; rather, the term also includes a range of temperatures within the span of temperatures from X to Y during the time of heating.
[0108] In another aspect, the present application provides a method for preparing a cathode active material as described herein, comprising: A. preparing one or more single crystals of a first component, comprising the steps of: (i) providing one or more lithium precursor compounds and one or more transition metal precursor compounds, (ii) contacting and milling the precursor compounds to form a milled mixture; (iii) calcining the milled mixture to provide a calcined mixture; B. preparing second crystalline particles of an anode active material, comprising the steps of: (i) providing one or more transition metal compounds, (ii) precipitating the transition metal to form a precipitate, and washing the precipitate to form a first precursor mixture; (iii) contacting the first precursor mixture with one or more lithium precursor compounds to form a second precursor mixture, and (iv) calcining the second precursor mixture.
[0109] C. combining the products obtained in A and B.
[0110] In the method of the present application, the products obtained in A and B can be combined as a slurry.
[0111] In the method of the present application, the products obtained in A and B can be combined in a weight ratio of 30:70 to 70:70, for example, a weight ratio of 40:60 to 60:40, for example, a weight ratio of 50:50.
[0112] The method of the present application can comprise one or more further steps. These one or more further steps can precede, follow or be interspersed with the steps listed herein.
[0113] In another aspect, the present application provides a battery comprising a cathode active material, the cathode active material comprising: (a) first crystalline particles, wherein the first crystalline particles have a spinel structure and have the formula Li x Ni y Mn 3-x-y- z D z O4, wherein 0.95 < x < 1.05; and 0.45 < y < 0.50, and 0 < z < 0.20, wherein D is a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W and mixtures thereof, and the first crystalline particles have a particle size of no more than 3 pm, measured as arithmetic average of the minimum Feret diameter of the particles using a scanning electron microscope, (b) second crystalline particles, wherein the second crystalline particles comprise a material having a spinel structure having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’ O4, wherein: 0.95 < x' < 1.05; 0.43 < y' < 0.47 and 0 < z' < 0.20, wherein D' is a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W and mixtures thereof, and the average particle size of the second crystalline particles is at least 3 times the average particle size of the first crystalline particles, measured as arithmetic average of the minimum Feret diameter of the particles using a scanning electron microscope, wherein y > y'.
[0114] Experimental part
[0115] In the following, exemplary and non-limiting embodiments of the present application are described in the form of experimental data. Examples 1-4 relate to the preparation method of the cathode active material. Example 5 describes a method to measure the minimum Feret diameter. Example 6 describes a method for obtaining SEM images of electrode cross sections. Example 7 describes a method to determine the tap density of the cathode active material. Example 8 relates to electrochemical characterisation. Example 9 describes the determination of the Ni and Mn content in the spinel and Example 10 provides some data and results for the claimed product, as well as comparative data.
[0116] Example 1 - Synthesis of cathode active material - small-Ni435
[0117] MnO2(269.5 g corresponding to 3.1 mol of Mn), basic Ni(OH) x (CO3) y(133 g corresponding to 0.9 mol of Ni) and Li2CO3(73,9 g corresponding to 2.0 mol of Li) and 1 L of water and ball-milled in a planetary ball mill (600 rpm, 30 minutes of reverse rotation) to form a slurry with a molar ratio Li:Ni:Mn = 1.00:0.45:1.55. Then, the mixture was dried at 120 °C for 12 hours. Then, the powder was mixed in a mortar for 15 minutes to obtain a precursor. 20 g of the precursor were heated in a 50 mL crucible at 900 °C for 3 hours and then cooled to room temperature at 1.5 °C / min. The product was disintegrated in a mortar for 15 minutes and sieved through a 45 micron sieve to obtain a cathode active material consisting of LNMO. A representative SEM image of the sample is shown in Figure 1. The arithmetic mean of the minimum Feret diameter of the material was determined to be 0.66 pm as described in Example 5. Based on the electrochemical characterizations described in Example 6, the stoichiometric ratio of the obtained LNMO material was determined to be Li 1.00 Ni 0.435 Mn 1.565 O4. Therefore, this sample was called small-Ni435.
[0118] Example 2 - Synthesis of a cathode active material - small-Ni470
[0119] MnO2(264.3 g corresponding to 3.04 mol of Mn), basic Ni(OH) x (CO3) y (141.9 g corresponding to 0.96 mol of Ni) and Li2CO3(73,9 g corresponding to 2.0 mol of Li) and 1 L of water and ball-milled in a planetary ball mill (600 rpm, 30 minutes of reverse rotation) to form a slurry with a molar ratio Li:Ni:Mn = 1.00:0.48:1.52. Then, the mixture was dried at 120 °C for 12 hours. Then, the powder was mixed in a mortar for 15 minutes to obtain a precursor. 20 g of the precursor were heated in a 50 mL crucible at 900 °C for 3 hours and then cooled to room temperature at 0.5 °C / min. The product was disintegrated in a mortar for 15 minutes and sieved through a 45 micron sieve to obtain a cathode active material consisting of LNMO. The particle morphology and size of the material were the same as for the small-Ni435 sample of Example 1. Based on the electrochemical characterizations described in Example 6, the stoichiometric ratio of the obtained LNMO material was determined to be Li 1.00 Ni 0.47 Mn 1.53 O4. Therefore, this sample was called small-Ni470.
[0120] Example 3 - Synthesis of a cathode active material - large-Ni435
[0121] Example 1 - Synthesis of a cathode active material + and SO4 2- ions. 940 g of the co-precipitated Ni,Mn-carbonate particles were mixed with 150 g of Li2CO3 (corresponding to Li:Ni:Mn = 1.00:0.45:1.55) and ethanol to form a viscous slurry. The slurry was shaken in a paint shaker for 3 minutes to obtain complete de-agglomeration and mixing of the particulate material. The slurry was poured into a tray and allowed to dry at 80 °C. The dried material was further de-agglomerated by shaking in a paint shaker for 1 minute to obtain a free-flowing homogeneous powder mixture. The powder mixture was heated in a furnace to 550 °C at a ramp of 2.5 °C / min under nitrogen flow. The powder was heated at 550 °C for 10 hours. Thereafter, the powder was treated in air at 550 °C for 10 hours. The temperature was ramped to 950 °C at a ramp of 2.5 °C / min. The temperature of 950 °C was maintained for 10 hours and ramped down to room temperature at a ramp of 1.5 °C / min.
[0122] The powder was again de-agglomerated by shaking in a paint shaker for 6 minutes and passed through a 45 micron sieve to obtain a cathode active material consisting of LNMO. SEM images of the sample are shown in Figure 2. The arithmetic mean of the minimum Feret diameter of the material was 8 pm. Based on the electrochemical characterisation described in Example 6, the stoichiometric ratio of the obtained LNMO material was determined to be Li 1.00 Ni 0.435 Mn 1.565 O4. Accordingly, this sample was referred to as large-Ni435.
[0123] Example 4 - Synthesis of a cathode active material
[0124] Example 4 - Synthesis of a cathode active material + and SO4 2-Ni, Mn-carbonates. 940.5 g of the co-precipitated Ni, Mn-carbonate particles were mixed with 150 g of Li2CO3 (corresponding to Li:Ni:Mn = 1.00:0.48:1.52) and ethanol to form a viscous slurry. The slurry was shaken in a paint shaker for 3 minutes to obtain complete de-agglomeration and mixing of the particulate material. The slurry was poured into a tray and allowed to dry at 80 °C. The dried material was further de-agglomerated by shaking in a paint shaker for 1 minute to obtain a free-flowing homogeneous powder mixture. The powder mixture was heated in a furnace to 550 °C at a ramp of 2.5 °C / min under nitrogen flow. The powder was heated at 550 °C for 10 hours. Thereafter, the powder was treated in air at 550 °C for 10 hours. The temperature was ramped to 950 °C at a ramp of 2.5 °C / min. The temperature of 950 °C was maintained for 10 hours and ramped to room temperature at a ramp of 0.5 °C / min.
[0125] The powder was again de-agglomerated by shaking in a paint shaker for 6 minutes and passed through a 45 micron sieve to obtain a cathode active material consisting of LNMO. The particle morphology and size of the material was the same as the large-Ni435 sample of Example 3. Based on the electrochemical characterisation described in Example 6, the stoichiometric ratio of the LNMO material obtained was determined to be Li 1.00 Ni 0.47 Mn 1.53 O4. Accordingly, this sample was referred to as large-Ni470.
[0126] Example 5 - Material Characterisation
[0127] The material was embedded in epoxy resin and polished to a flat surface. SEM images were acquired on a Zeiss Gemini SEM 500 equipped with a field emission gun (FEG) using an acceleration voltage of 10 kV and an energy selective backscatter (ESB) ESB detector, which is a backscatter electron detector type. The pixel size was 0.01 pm / pixel. A total of 25 images were acquired and stitched into a high resolution image of 4930 pixels x 3697 pixels corresponding to an image area of 48 pm x 36 pm. An image of the small-Ni435 prepared as described in Example 1 is shown in Figure 3. The images were analysed according to the following procedure, detecting and analysing a total of 663 particles 36 pm. An image of the small-Ni435 prepared as described in Example 1 is shown in Figure 3. The images were analysed according to the following procedure, detecting and analysing a total of 663 particles
[0128] The images were analysed using ImageJ software (https: / / imagej.nih.gov). The procedure was: Threshold conversion and segmentation using the “Otsu algorithm” Binary process applied, “fill holes” Apply binary process, "Erode" 8 times Apply binary process, "Dilate" 6 times.
[0129] Use "Analyze Particles" with no size limit
[0130] Fill Holes is used to fill possible holes inside the particles. The erosion followed by the dilation step is used to remove possible noise and ensure that tightly packed particles are separated.
[0131] Size measurements: Mean Minimum Feret 0.66 pm Mean Equivalent Circle Diameter 0.84 pm Number of Particles 663 Example 6 - Characterization of electrodes of mixed materials Figure 4 shows SEM images of cross-sections of electrodes with mixture 1 (small-Ni435 and large-Ni435). Cross-sections of the pressed electrodes were prepared by embedding in epoxy resin and polishing to a flat surface perpendicular to the electrode surface.
[0132] Example 7 - Pressed density.
[0133] The pressed density of the cathode active material powder was measured as follows. 3.00 g of material was loaded into a die with a cylindrical body (16 mm in diameter). The power was compressed by applying pressure (1-2 tons / cm 2 ) on a punch that fits in the die with the body. By measuring the position of the punch, the volume of the powder could be determined and thus the pressed density. The pressed density as a function of applied pressure for the materials in Example 1, Example 2, and a 50:50 mixture of these two materials is shown in Figure 5 and Tables 1-3.
[0134] Example 8 - Electrochemical characterization
[0135] In 2032 button cells, thin composite cathodes and anodes using metallic lithium (half cells) and lithium titanate (LTO) (full cells) respectively were electrochemically tested. Thin composite cathodes were prepared by thoroughly mixing 92 wt% of the cathode active LNMO material with 4 wt% of Super P® carbon black (Timcal) and 4 wt% of PVdF binder (polyvinylidene fluoride, Arkema) in NMP (N-methyl pyrrolidone) to form a slurry. The slurry was spread on carbon-coated aluminum foil using a doctor blade with a gap of 100-200 pm and dried at 80 °C for 12 hours to form a thin film. Electrodes with a diameter of 14 mm and loaded with about 12 mg of cathode active material were cut from the dried film, pressed in a hydraulic pellet press (20 mm in diameter; 3 tons) and vacuum dried at 120 °C for 10 hours in an argon-filled glovebox. LTO electrodes were purchased from Custom Cells Itzehoe gmbh. In the case of half cells, button cells were assembled in an argon-filled glovebox (<1 ppm of O2 and H2O) using a glass fiber separator, electrolyte containing 1 mole of LiPF6 in EC:DEC (weight ratio of 1 :1) and a 500 pm thick lithium disc as anode and in the case of full cells, button cells were assembled using a Celgard H2010 separator, electrolyte containing 1 mole of LiPF6 in EC:DEC (weight ratio of 1 :1) and a LTO electrode with a diameter of 15 mm and loaded corresponding to a balanced N / P of 1.2.
[0136] The electrochemical lithium insertion and extraction was monitored using an automated cyclic data logging system (Maccor) operated in constant current mode. The (dis)charge current is given in C. The definition of 1 C is the theoretical current needed to (dis)charge the battery in 1 hour.
[0137] The electrochemical test of the half cells comprised 4 formation cycles (1 cycle 0.2C / 0.2C (charge / discharge), 1 cycle 0.5C / 0.5C and 2 cycles 0.5C / 1C) 0.5C / 0.2C), 9 power test cycles (3 cycles 0.5C / 1C, 3 cycles 0.5 / 5C, 3 cycles 0.5C / 10C), followed by one 0.1C / 0.1C cycle to measure the capacity and then 50 0.5C / 1C cycles to measure the degradation. The electrochemical test of the full cells comprised 3 formation cycles at 0.1C / 0.1C to measure the battery capacity.
[0138] The half cells were cycled in a voltage interval of 3.5-5.0 V, which means that the upper cut-off voltage for charging was 5.0 V and the lower cut-off voltage for discharging was 3.5 V.
[0139] LNMO-LTO batteries were cycled in the voltage interval 1.7-3.4 V and 2.8-3.4 V.
[0140] The LNMO materials tested and shown in Figures 6-11 are small particles (small-Ni435) and 2 (small-Ni470) prepared according to Example 1 and large particles (large-Ni435) and 4 (large-Ni470) prepared according to Example 3 and mixtures thereof, where the number refers to the nickel content in the spinel material determined by electrochemical characterization as described in Example 9.
[0141] When testing mixtures, both LNMO materials were added to the slurry simultaneously in a 50:50 weight ratio. Tests of three material mixtures are presented. These are large-Ni435 + small-Ni435 (mixture 1), large-Ni470 + small-Ni435 (mixture 2) and large-Ni435 and small-Ni470 (mixture 3).
[0142] The LNMO materials tested and shown in Figure 12 were synthesized as described in Examples 1 and 3, but with minor modifications to the recipe to achieve different nickel contents in the spinel.
[0143] The capacity is given relative to the LNMO content in the electrode as the charge accumulated during discharge from the upper voltage limit to the lower voltage limit. The capacity unit is mAh / (g LNMO).
[0144] The degradation of the battery is given as the relative capacity loss after 100 charge-discharge cycles. The degradation unit is % / 100 cycles.
[0145] The electrochemical data of the half-cells are shown in Figures 6-9 and 12 and the data of the LNMO-LTO batteries are shown in Figures 10-11.
[0146] The voltage curves shown in Figures 6, 8 and 10 were collected by the battery tester and used to calculate the capacity and average voltage.
[0147] In Figures 7, 9 and 11, the capacity as a function of charge-discharge cycles is plotted. These data were used to determine the degradation of the batteries.
[0148] Figure 12 shows the calculated degradation of a variety of samples with different particle sizes and different nickel contents in the spinel.
[0149] The specific energy density of the cathode active material in the battery is determined by multiplying the average voltage by the capacity.
[0150] The energy density of the cathode active material in the battery is determined by multiplying the specific energy density by the pressed density. The determination of the pressed density is described in Example 7.
[0151] Table 1-4 summarizes the capacity, average voltage, degradation, and energy density.
[0152] Example 9 - Determination of Ni and Mn content in spinel
[0153] Depending on the preparation of the lithium cathode active material, the content of Ni and Mn in the spinel of the lithium cathode active material can differ from the volumetric values determined using ICP and the like. This example shows that the content of Ni and Mn in the spinel of the lithium cathode active material can be determined using two different methods based on electrochemistry and diffraction, respectively.
[0154] These methods take advantage of the fact that a change in the Mn / Ni ratio changes the ratio between Mn 3+ and Mn 4+ . Based on the assumption that the oxidation state of Li is 1+, Ni is 2+, and O is -2, it is clear that the average oxidation state of Mn in Li x Ni y Mn 2-y O4 is (4 2-1 x-2 y) / (2-y). Using this, in the case of x = 1, the equation can be written as Li +1 Ni +2 y Mn +3 1-2y Mn +4 1+y Similar for the expression where x is not equal to 1.
[0155] Electrochemically, Mn 3+ can be reversibly oxidized to Mn + and back by extraction and insertion of Li 4+ during cycling, and Ni 2+ can be reversibly oxidized to Ni + and back by extraction and insertion of Li 4+ during cycling. Thus, two Li + / Ni 2+ and one Li + / Mn 3+ can be extracted (and subsequently inserted). In the case of x = 1, according to the equation Li +1 Ni +2 y Mn +3 1-2y Mn +4 1+yO4, the fraction of the capacity associated with Mn activity is thus given by (1 - 2y) / (1 - 2y + 2y) = (1 - 2y). For example, y = 0 corresponds to 0% capacity associated with Mn activity, and y = 0.45 and 0.4 correspond to 10% and 20% of the total capacity from Mn activity, respectively.
[0156] In LNMO, Mn 3+ / Mn 4+ reacts at about 4 V vs. Li / Li + and Ni 2+ / Ni 4+ reacts at about 4.7 V vs. Li / Li + and is observed. Thus, the measured capacity from 3.5 V to 4.3 V vs. Li / Li + is expected to correspond to Mn activity, compared to the total capacity from 3.5 V to 5 V vs. Li / Li + . As described in Example 8, the capacity at about 4 V is determined using the second discharge at a current of 74 mA / g (0.5 C). During the charging and discharging processes, the battery is not in equilibrium, and due to the internal resistance of the battery, the measured voltage can move upwards during the charging process and downwards during the discharging process. This effect is particularly evident when the voltage of the battery changes abruptly, so the fraction of Mn activity appears different depending on whether the analysis is based on the charge or the discharge. The true value will be between these two values, and a reasonable estimate is the average between the two. Figure 13 shows the discharge and charge voltage curves as a function of capacity at a current of 74 mA / g (0.5 C) for the second charge-discharge, as described in Example 8. The capacities Q 4V cha and Q 4V dis are used, corresponding to the voltage of 4.3 V during the charge and discharge, respectively. The fraction of Mn activity is given by (Q tot dis + Q 4V cha - Q tot dis ) / (2 4V dis ). This value is denoted as the “4 V plateau”. Q tot dis .
[0157] diffraction
[0158] Mn 3+ and Mn 4+ ions differ in size, with Mn 3+maximum, and this affects the lattice parameter of the spinel. Powder x-ray diffraction data were collected on a Phillips PW1800 instrument system working in Bragg-Brentano mode in theta-2theta geometry using Cu K alpha radiation (l = 1.541 A). The observed data required correction for experimental parameters that caused a shift in the observed peak positions, which were used to calculate the lattice parameter. This was achieved using the full profile fundamental parameter method implemented in TOPAS software from Bruker. The spinel lattice parameter was therefore determined with an uncertainty of approximately 5 / 10000 A, which was sufficient to determine the amount of Mn 3+ and hence the amount of Mn and Ni.
[0159] The effectiveness of both methods was demonstrated by comparing the electrochemically determined 4V plateau with the a-axis determined using XRD. Figure 14 shows this comparison, and the linear correlation directly links the increase in volume with the increase in Mn 3+ Figure 15 shows the same data as Figure 14, but the x-axis is converted to the nickel content of the spinel, y, using the 4V plateau given by (1 - 2y) as described above. The relationship between the a-axis determined using XRD measurements and the ratio between Mn and Ni given by y determined from the 4V plateau can be fitted as a linear relationship: a = -0.1932 y + 8.2627. The LNMO materials tested and demonstrated in Figures 14 and 15 were synthesised as described in Examples 1 and 3, but with minor modifications to the formulation to achieve different nickel contents in the spinel.
[0160] The effectiveness of both methods was further verified by comparing the measured nickel content of selected samples with direct measurements of the Ni and Mn content inside the particles using scanning transmission electron microscopy-energy dispersive X-ray spectroscopy.
[0161] Example 10 - Data comparison
[0162] Table 1 : Single LNMO material - half cells
[0163] Table 2: Mixed materials - half cells:
[0164] Table 3: Mixed LNMO and high voltage negative (LTO)
[0165] Table 4: Comparison of key numbers for energy density and degradation for Tables 1-3
[0166] Based on Tables 1-4 and Figures 1-12, several observations are highlighted to illustrate the best effects of achieving high energy density and low degradation by varying the particle size and nickel content of the LNMO spinel cathode active material: The energy density can be maximized by increasing the average voltage, specific capacity, and powder density in the electrode.
[0167] The average voltage is increased by increasing the nickel content in the spinel, for example, as shown in Table 1, by changing the nickel content in the spinel from y = 0.435 to y = 0.470, the average voltage is increased from 4.60 V to 4.66 V, an increase of 1.3%.
[0168] The specific capacity is almost unchanged by the nickel content of the spinel, but in some cases, as shown in Figure 11 and Table 3, a limited voltage range is favorable for degradation, in which case the specific capacity within that range increases with the nickel content in the spinel, for example, for LNMO-LTO batteries, within the range of 2.8 V to 3.4 V, by increasing the nickel content from y = 0.435 to y = 0.470 in the small particles of the 50:50 mixture, the specific capacity is increased from 116 mAh / g to 122 mAh / g, an increase of 5%, as shown in Table 3.
[0169] The powder density is increased by mixing small and large particles, for example, by mixing small particles with large particles in a 50:50 mixture in the blend, the powder density is increased from 2.5 g / cm 3 to 3.0 g / cm 3 , an increase of 20%, as shown by comparing Table 1 and Table 2.
[0170] The degradation increases with the nickel content, but if the particles are small enough, the degradation is independent of the nickel content in the spinel. This is embodied in Tables 1 and 2 and Figures 7, 9, 11, and 12.
[0171] Therefore, the best combination is a mixture of small particles with high nickel content and large particles with low nickel content. According to the materials described in Examples 1-4, the best combination is a mixture of large-Ni435 with small-Ni470.
[0172] Table 4 shows a comparison of how the particle size and nickel content in the spinel affect the energy density. In general, the energy density is improved by about 20% by using a combination of small and large particles. Depending on the chemistry and operation of the battery, increasing the nickel content in the small LNMO particles can surprisingly increase the energy density by an additional 1-6%.
[0173] Various modifications and variations of the application will be apparent to those skilled in the art without departing from the scope and spirit of the application. Although the application has been described in connection with specific preferred embodiments, it should be understood that the application as claimed should not be unduly limited to such specific embodiments. Indeed, various modifications of the described modes of carrying out the application that are obvious to those skilled in chemistry or related fields are intended to be within the scope of the following claims.
Claims
1. A cathode active material comprising: (a) first crystalline particles, wherein the first crystalline particles have a spinel structure and have the formula Li x Ni y Mn 3-x-y- z D z 04, wherein 0.95≤x≤1.05; 0.45≤y≤0.50, and 0≤z≤0.20, wherein D is a dopant selected from the group consisting of B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W, and mixtures thereof, and the first crystalline particles have a particle size of no more than 3 pm, measured as the arithmetic average of the smallest Feret diameters of the particles using a scanning electron microscope, (b) second crystalline particles, wherein the second crystalline particles comprise a material having a spinel structure and having the formula Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’ O4, wherein: 0.95 < x' < 1.05; 0.43 < y' < 0.47 and 0 < z' < 0.20, wherein D' is a dopant selected from B, N, F, Mg, Al, Nb, Si, P, La, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Mo, Sn, W and mixtures thereof, and the average particle size of the second crystalline particles is at least 3 times the average particle size of the first crystalline particles, measured as the arithmetic mean of the smallest Feret diameter of the particles measured using a scanning electron microscope, wherein y > y'.
2. The cathode active material according to claim 1, wherein 0.98 < x < 1.
02.
3. The cathode active material according to claim 1 or 2, wherein x is 1.
4. The cathode active material according to any one of the preceding claims, wherein 0.46 < y < 0.
50.
5. The cathode active material according to any one of the preceding claims, wherein 0.48 < y < 0.
50.
6. The cathode active material according to any one of the preceding claims, wherein 0 < z < 0.
05.
7. The cathode active material according to any one of the preceding claims, wherein D is a dopant selected from B, Mg, Al, Nb, Si, P, La, S, Ti, Fe, Co, Cu, Zn, Zr, Mo, Sn, W and mixtures thereof.
8. The cathode active material according to any one of claims 1 to 5, wherein z = 0.
9. The cathode active material according to any one of the preceding claims, wherein the first crystalline particles have a particle size of no more than 2 pm.
10. The cathode active material according to any one of the preceding claims, wherein the second crystalline particles are polycrystalline second particles.
11. The cathode active material according to any one of the preceding claims, wherein 0.98 < x' < 1.
02.
12. The cathode active material according to any one of the preceding claims, wherein x' is 1.
13. The cathode active material according to any one of the preceding claims, wherein 0.44 < y' < 0.
47.
14. The cathode active material according to any one of the preceding claims, wherein 0.45 < y' < 0.
46.
15. The cathode active material according to any one of the preceding claims, wherein 0 < z' < 0.
05.
16. The cathode active material according to any one of the preceding claims, wherein D' is a dopant selected from B, Mg, Al, Nb, Si, P, La, S, Ti, Fe, Co, Cu, Zn, Zr, Mo, Sn, W and mixtures thereof.
17. The cathode active material according to any one of claims 1 to 15, wherein z' = 0.
18. The cathode active material according to any one of the preceding claims, wherein the first crystalline particles have a particle size of 0.5 pm to 2 pm, measured as the arithmetic mean of the smallest Feret diameter of the particles measured using a scanning electron microscope; the second crystalline particles have an average particle size of 5 pm to 10 pm, measured as the arithmetic mean of the smallest Feret diameter of the particles measured using a scanning electron microscope.
19. The cathode active material according to any one of the preceding claims, wherein the first crystalline particles have a particle size of no more than 1 pm, measured as the arithmetic mean of the smallest Feret diameter of the particles measured using a scanning electron microscope; the second crystalline particles have an average particle size of at least 3 pm, measured as the arithmetic mean of the smallest Feret diameter of the particles measured using a scanning electron microscope.
20. The cathode active material according to any one of the preceding claims, wherein the first crystalline particles are single crystalline particles.
21. The cathode active material according to any of the preceding claims, wherein the second crystalline particles comprise a material having a spinel structure and a formula of Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’ O4, the content of the material of formula Li x’ Ni y’ Mn 3-x’-y’-z’ D’ z’ O4 is at least 94 wt.%, such as at least 96 wt.%, such as at least 98 wt.%, based on the weight of the second crystalline particles.
22. A battery comprising the cathode active material according to any one of claims 1 to 21.
Citation Information
Patent Citations
High-voltage positive electrode material having a spinel structure based on nickel and manganese for lithium cell batteries
US7754384B2
Optimised positive electrode material for lithium cell batteries, method for the production thereof, electrode, and battery for implementing said method
US8404381B2
Lithium positive electrode active material
WO2020127543A1